Curbing Illicit Financial Flows in Commodity Trade and Beyond - Gilles Carbonnier; Fritz Brugger; Elisabeth Bürgi Bonanomi; Fred M. Dzanku; Stabandith Insisienmay (Revue Internationale de Politique de Développement, 2024)
Establishing a more transparent, effective and equitable and framework for trade and taxation is crucial to enabling commodity exporting states to mobilise domestic resources for sustainable development. The current drive to reform the global governance of taxation offers opportunities, but takes place in the context of heightened North–South tensions, reduced trust in multilateralism and calls for deeper decolonisation. Drawing on a six-year multidisciplinary research project involving academic institutions from commodity exporting and trading countries, this chapter presents a research framework that the authors used for the study of illicit financial flows associated with commodity trade. It discusses major findings, and recommendations as to how to counter the ensuing tax base erosion in resource-rich developing countries. The latter can consider a range of policies and innovative measures to rein in commodity trade mispricing. But this is not enough. States hosting major trading and financial centres have to simultaneously address a range of pull factors. At the global level, fair taxation reform is key and must preserve a sovereign policy space, in which commodity exporting states may adopt context-specific solutions aligned with their institutional capacities. Finally, this chapter introduces the thematic volume of International Development Policy on illicit financial flows in the commodity sector and beyond.